2003
DOI: 10.1007/s00432-003-0461-7
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring lignans efficiently induce apoptosis in colorectal tumor cells

Abstract: Plant-derived lignans caused cell loss by apoptosis in colorectal adenoma and carcinoma cells. Nordihydroguaiaretic acid (NDGA), commonly used for the inhibition of lipoxygenase isoenzymes, showed the strongest growth inhibition with an IC50 of 1.9+/-0.5 microg followed by epiashantin (IC50=9.8+/-4.5 microM) and arctigenin (IC50=16.5+/-8.5 microM). The lignans caused a time- and dose-dependent loss of mitochondrial membrane potential (MMP), down regulation of the anti-apoptotic protein bcl(xl) and an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
1
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 33 publications
1
69
1
4
Order By: Relevance
“…The molecular mechanism behind anticancer activity of lignans is not yet well characterized. Lignans have been reported to induce downregulation of the anti-apoptotic Bcl-2 proteins (Hausott et al, 2003) and to inhibit casein kinase II and protein kinase C a (Yokoyama et al, 2003). They can act as antioxidants protecting cells from oxidative stress (Kitts et al, 1999), or as inhibitors of steroid metabolizing Lignans sensitize prostate cancer cells to TRAIL E Peuhu et al enzymes (Adlercreutz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The molecular mechanism behind anticancer activity of lignans is not yet well characterized. Lignans have been reported to induce downregulation of the anti-apoptotic Bcl-2 proteins (Hausott et al, 2003) and to inhibit casein kinase II and protein kinase C a (Yokoyama et al, 2003). They can act as antioxidants protecting cells from oxidative stress (Kitts et al, 1999), or as inhibitors of steroid metabolizing Lignans sensitize prostate cancer cells to TRAIL E Peuhu et al enzymes (Adlercreutz et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies show an inverse association between dietary intake of lignans and the risk of cardiovascular disease [10,11]. Lignans also have potential protective roles against cancer in breast [12], prostate [13], and colon [14,15]. A study done in rats showed that exposure of 10% flaxseed (SDG-rich plant seeds) or the equivalent SDG levels during suckling suppressed chemical carcinogen 7, 12-dimethylbenz(α)anthracene (DMBA)-induced mammary tumorigenesis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Schisandrin C was obtained as colorless needles (from MeOH), C 22 at ‰ = 1.72 (1H, m) are indicative of the C-8 and C-7 methyl groups, respectively (Fig. 1B).…”
Section: Resultsmentioning
confidence: 99%
“…The seeds and fruits of S. chinensis are enriched in lignans, and more than 40 lignans have been isolated from this plant (15)(16)(17)(18)(19)(20)(21). Some lignans have previously been reported to induce cell cycle arrest and apoptosis in human cancer cell lines including leukemia cells (22)(23)(24)(25)(26). However, the underlying molecular mechanisms for their putative therapeutic effects are not clear.…”
Section: Introductionmentioning
confidence: 99%